Modal dan Makna Kerja Dalang Wayang Potehi di Semarang: Kisah Hidup Thio Tiong Gie - Hezti Insriani (Jurnal Kajian Seni, 2016)
This study is about the work of Chinese glove puppet puppeteer in Semarang (Thio Tiong Gie). This study showed that he had been using several capitals in his work such as social and economic, and also cultural and symbolic capital. From Thio Tiong Gie’s case, we can see that cultural, social, and symbolic capitals are important for art worker’s practice. They had been used by art worker in his work for exchange with economic capital besides accumulation of those capitals. There are many meanings in Thio Tiong Gie’s work.For Thio Tiong Gie, the meanings of work are about economic, phsycologic, and religious meanings. This study has given perspective to see how the work activity of Chinese glove puppet puppeteer is, not only concerning with the product of the work.